Analysis of damage in steel bar for reinforced concrete deformed at varied strain rates by continuum damage mechanism - Lamo , Werachai (Bulletin of Applied Sciences, 2022)
This research study aimed to examine damage evolution in steel bar for reinforced concrete by continuum damage mechanism from and throughout deforming process at varied strain rates from 0.001 s-1, 0.005 s-1, 0.01 s-1 to 0.02 s-1. From the research study, the increase of the strain rates in the beginning (0.001 s-1 to 0.01 s-1) had a significant effect on the development of the damage, approximately 0.33 and 0.18. In other words, the damage rate greatly increased in the initial stage when the stain rate increased. In the later stage, the rising of the strain rates from 0.01 s-1 to 0.02 s-1 had a slighter effect on the development of the damage, approximately 0.17 and 0.11. In other words, the damage rate increased lower when the strain rate rose additionally.